PENGARUH VARIASI ARAH SERAT DAN FRAKSI VOLUME SERAT PANDAN DURI TERHADAP KEKUATAN TARIK DAN IMPAK SEBAGAI MATERIAL ALTERNATIF HELM SNI - Aditya Rachman; Juanda Juanda; yuli Dharta (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Pandan thorn with the term (Pandanus tectorius) is a bush plant with climbing stems and has a height of 11 m. This research was conducted to obtain data on the tensile strength and impact strength of pandan thorn fiber with variations in fiber direction and volume fraction. This research is expected to be useful for SNI helmet materials. The maximum value of tensile strength is 41.33 MPa in the vertical fiber direction and the fiber volume fraction is 12.5%. While the lowest tensile strength value is 8.44 MPa using horizontal fiber direction with a fiber volume fraction of 7.5%. The largest impact strength is 0.0616 J/mm2 in the vertical direction of fiber with a fiber volume fraction of 12.5% and the smallest impact strength is 0.0216 J/mm2 in the horizontal fiber direction with a fiber volume fraction of 7.5%. In this test, compared with the results of the tensile and impact strength testing of SNI helmets of 33.93 MPa and 0.00972 J/mm2, the specimens passed the material test for SNI helmets.